Integrating metabolomics, bionics, and culturomics to study probiotics-driven drug metabolism - Li, Bohai; Kwok, Lai-Yu; Wang, Dandan; Li, Lu; Guo, Shuai; Chen, Yongfu (Frontiers in Pharmacology, 2023)
Many drugs have been shown to be metabolized by the human gut microbiome, but probiotic-driven drug-metabolizing capacity is rarely explored. Here, we developed integrated metabolomics, culturomics, and bionics framework for systematically studying probiotics-driven drug metabolism. We discovered that 75% (27/36 of the assayed drugs) were metabolized by five selected probiotics, and drugs containing nitro or azo groups were more readily metabolized. As proof-of-principle experiments, we showed that Lacticaseibacillus casei Zhang (LCZ) could metabolize racecadotril to its active products, S-acetylthiorphan, and thiorphan, in monoculture, in a near-real simulated human digestion system, and in an ex vivo fecal co-culture system. However, a personalized effect was observed in the racecadotril-metabolizing activity of LCZ, depending on the individual's host gut microbiome composition. Based on data generated by our workflow, we proposed a possible mechanism of interactions among LCZ, racecadotril, and host gut microbiome, providing practical guidance for probiotic-drug co-treatment and novel insights into precision probiotics.